Formation of complex phosphates K₂MᴵᴵᴵSn(PO₄)₃ from solutions in melts under crystallization conditions - Zatovsky, I.V.; Slobodyanik, N.S.; Ushchapivska, T.I.; Han, W. (Functional Materials, 2017)
This article studies the regularities of formation of isostructural to langbeinite phosphates from solutions in melts under crystallization conditions for K₂O-P₂O₅-M<m^>III₂O₃-SnO₂ (MIII - Fe, Cr) and K₂O-P₂O₅-LnF₃-SnO₂ (Ln - Y, REE) systems. Based on X-ray powder diffraction method the phase composition of synthesized samples and lattice parameters have been determined for a number of new compounds with common composition K₂MIIISn(PO₄)₃. Analysis of obtained results shows that the crystallochemical criterion for formation of langbeinite-type framework on the basis of different multivalent metals is the difference in their ionic radii up to 35 %.